FADD/MORT1 and caspase-8 are recruited to TRAIL receptors 1 and 2 and are essential for apoptosis mediated by TRAIL receptor 2 - Sprick, Martin; Weigand, Markus A.; Krammer, Peter H.; Walczak, Henning (Immunity, 2000)
Apoptosis induced by tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL/APO-2L) has been shown to exert important functions during various immunological processes. The involvement of the death adaptor proteins FADD/MORT1, TRADD, and RIP and the apoptosis-initiating caspases-8 and -10 in death signaling by the two death-inducing TRAIL receptors 1 and 2 (TRAIL-R1 and TRAIL-R2) are controversial. Analysis of the native TRAIL death-inducing signaling complex (DISC) revealed ligand-dependent recruitment of FADD/MORT1 and caspase-8. Differential precipitation of ligand-stimulated TRAIL receptors demonstrated that FADD/MORT1 and caspase-8 were recruited to TRAIL-R1 and TRAIL-R2 independently of each other. FADD/MORT1- and caspase-8-deficient Jurkat cells expressing only TRAIL-R2 were resistant to TRAIL-induced apoptosis. Thus, FADD/MORT1 and caspase-8 are essential for apoptosis induction via TRAIL-R2.